Forms of acknowledgement of debt in Malaysia: the legal implications - Mohamed, Duryana (2015)
Payment of debt is regarded as an obligation and it must be paid according to the terms and conditions of business or loan agreements. Failure to pay debt or to refund the outstanding sum will result with many consequences such as declaration of bankrupt and winding up company. Usually, the debtors or borrowers will comply with the terms of the loan agreement. But if they refuse to pay and ignore the request made by the creditor, the latter may proceed with legal action against the debtor. The debtor will normally argue that the action is time barred or the claim is unreasonable. However, if there was an acknowledgement of debt by the debtor, the creditor will rely on the acknowledgement made by the debtor in order to proceed with his claim. Based on court decisions, there are many forms or methods of debt acknowledgement by the creditors in Malaysia. This paper will examine various forms of debt acknowledgement and the legal implications of such acknowledgment.